2001
DOI: 10.1002/ajim.10019
|View full text |Cite
|
Sign up to set email alerts
|

Risk of shoulder tendinitis in relation to shoulder loads in monotonous repetitive work

Abstract: The results indicate that workers with repetitive tasks have increased risk of shoulder tendinitis, which partially can be attributed to force requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 24 publications
9
96
2
3
Order By: Relevance
“…The fact that UE-MSDs are a common and fairly minor health problem might explain why subjects without a UE-MSD (maybe feeling less affected by the study) less often partici-pated a few years after their inclusion in the study, as reported in women by Goldberg et al in a French cohort 36) . This lower participation would result in an overestimation of risks of UE-MSDs only if participation is higher among workers exposed to UE-MSDs than others 37) . In our study, a higher level of initial exposure may have positively influenced participation of both genders, as found elsewhere 38) .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that UE-MSDs are a common and fairly minor health problem might explain why subjects without a UE-MSD (maybe feeling less affected by the study) less often partici-pated a few years after their inclusion in the study, as reported in women by Goldberg et al in a French cohort 36) . This lower participation would result in an overestimation of risks of UE-MSDs only if participation is higher among workers exposed to UE-MSDs than others 37) . In our study, a higher level of initial exposure may have positively influenced participation of both genders, as found elsewhere 38) .…”
Section: Discussionmentioning
confidence: 99%
“…Tendon injuries are common and affect a substantial portion of recreational and professional athletes and those in many occupations involving repetitive work [16,37,60,79,102]. Tendinopathy (often called tendinitis or tendinosis) is the most common tendon disorder [86,99].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that neck-shoulder complaints and occupational biomechanical shoulder exposures would each increase the risk. Table 1 presents the original studies I-IX (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and their contribution to the MRD, which comprises 39 590 persons. A total of 265 persons participated in two studies, and one person participated in three; for these persons, we selected the questionnaire dataset that was most informative for the present study.…”
Section: Svendsen Et Almentioning
confidence: 99%